Evaluation of professional skills of elementary school teachers - Zahra Danesh pazhouh; Valiollah Farzad (فصلنامه نوآوری‌های آموزشی, 2006)
This research was conducted to evaluate professional skills of elementary school teachers in Tehran. We investigated the potential strengths and weaknesses of their teaching skills in order to propose appropriate solutions to reduce weaknesses and improve strengths of teaching skills.